Penambahan bakasang pada pakan benih sidat (Anguilla marmorata) untuk meningkatkan sistem imun non spesifik - Pinoke, Steven A.J; Tumbol, Reiny A; Kolopita, Magdalena E.F (Universitas Sam Ratulangi, 2015)
This study was aimed to examine the effect of immunostimulant bakasang (fermented product from fish) and to determine the optimal dose of bakasang in increasing the non-specific immune response of eels. The eels were obtained from Institute of Freshwater Aquaculture (BPBAT) Tatelu. Bakasang as immunostimulant ingredient contained Lactic Acid Bacteria (LAB) with the bacteria concentration of 105 CFU/ml was prepared by diluting with clean water to get the doses desired. The feed was subsequently mixed with the commercial fish feed in powder form and mixed well with water to form paste. This research used Two-ways ANOVA with 4 different types of treatments A (0 ml/kg feed), B (50 ml/kg feed), C (100 ml/kg feed), D (150 ml/kg feed) and 3 repetitions. The fish were feed with treatments diets for 3 weeks with a dose of 3% body weight per day with a frequency of twice a day (at 08:00 am) and the afternoon (16.00 pm). The parameters measured was Total Leukocyte Count (TLC) which was measured every week (t0, t1, t2, t3). The results indicated that the addition of bakasang on eels’feed gave a significant increased on TLC, and that the highest TLC was found in the dose of 100 ml/kg feed. This shows that the optimal dose of bakasang in increasing the TLC of eels was 100 ml/kg feed after administration of 3 weeks. Keywords: Eels, Bakasang, Total Leucocytes Count